Maternal stress as a risk factor for non-syndromic orofacial clefts: Systematic review and meta-analysis - Mona Talal AlSharif; Rana Abdullah Alamoudi; Heba Jafar Sabbagh (Elsevier, 2023)
Background: Non-syndromic orofacial clefts (NSOFC) are among the most common congenital malformations. Several studies have investigated the association between stress and NSOFC; however, they have reported different and heterogeneous results. Therefore, this systematic review was conducted to investigate the association between maternal periconceptional stress and non-syndromic orofacial clefts in infants.The research question was "Is maternal periconceptional stress an etiological factor for non-syndromic orofacial clefts in infants"? Methods: Search strategy, inclusion/exclusion criteria, and data extraction from studies reporting periconceptional maternal exposure to stress and NSOFC were implemented without language restrictions. The risks of bias in the identified studies was assessed, and this information was used in the sensitivity analyses to explain heterogeneity. A meta-analysis of the extracted data was performed. Results: Twelve eligible studies were included. Forest plot for meta-analysis of the association between maternal periconceptional exposure to stress and NSOFC among studies with adjustment for potential confounders showed a statistically significant association with an increased risk of NSOFC (odds ratio [OR]:1.17; P = 0.03), which was apparent for both cleft lip with and without palate (OR:2.07; P = 0.007) and cleft palate (OR:1.72; P = 0.003). There was a substantial heterogeneity between studies, which improved when analyzing only studies that were adjusted for potential confounders. Conclusion: Based on the currently available evidence, maternal exposure to periconceptional stress could be considered a risk factor for NSOFCs. Therefore, we strongly recommend research investigating the effect of stress caused by the coronavirus disease-2019 pandemic on the incidence of clefts.